Continuous Glucose Monitoring in Newly Diagnosed Type 2 Diabetes Patients Reveals a Potential Risk of Hypoglycemia in Older Men - Feng-fei Li; Bing-li Liu; Hong-hong Zhu; Ting Li; Wen-li Zhang; Xiao-fei Su; Jin-dan Wu; Xue-qin Wang; Ning Xu; Wei-Nan Yu; Qun Yuan; Guan-cheng Qi; et al. (Journal of Diabetes Research)
Objectives. We performed continuous glucose monitoring (CGM) to define the features of patients with newly diagnosed type 2 diabetes (T2D) before and after Continuous Subcutaneous Insulin Infusion (CSII) therapy. Methods. This was a retrospective analysis. Newly diagnosed T2D patients (106) were admitted from eight centers in China. They were divided into a younger patient group (<60 years) and an older patient group (≥60 years). Each group was further divided into male and female patients. CSII therapy was maintained for 3 weeks after the glycemic target was reached. CGM was performed 2 times before and after completion of insulin treatment. Results. CGM data showed the expected significant improvement of mean amplitude glycemic excursion (MAGE) with CSII therapy. The older patients had lower hourly glucose concentrations from 0200 to 0700 o’clock compared to the younger patients at baseline. Surprisingly, in the older patient group, the male patients had a potential risk of hypoglycemia after CSII therapy, especially during periods from 2300 to 2400 and 0400 to 0600. Conclusions. Our data suggested that older male patients with newly diagnosed T2D may have lower nocturnal glucose concentrations. This may potentially increase the risk of nocturnal hypoglycemia during CSII therapy. This study was registered with Chinese Clinical Trial Registry, number CliCTR-TRC-11001218.